Acemoglu, Johnson and Robinson’s Notion of Exogenous Imposition of Colonial Institutions onto Colonies— A Critique in the Light of Historical Evidence (The Pakistan Development Review, 2025)
This paper provides critique of Acemoglu, Johnson, and Robinson’s (2001, 2002) notion that rests on the hypothesis of exogenous imposition of colonial institutions onto their respective colonies based on conditions for their settlement. Our research brings forth the logical loopholes in Acemoglu, Johnson, and Robinson (AJR) by constructing arguments against the over-simplified assumption of exogenous imposition of colonial institutions in explaining the differences in development today. To prove our point, we build on two main arguments from history to show that some degree of endogeneity did indeed exist in colonial institutions that were imposed on the colonies. Our first argument revolves around the theme that how Atlantic slave trade evolved with colonialism and had meaningful technological and institutional consequences in the colonial metropolitan state. And these evolving conditions in coloniser’s mother country not only shaped incentives for mercantilist colonialism at one level and at the other became the base of institutional setup of progressive forms. In our second part of the argument, we demonstrate the role of native agency either in the form of local’s formal or informal pre-colonial institutions or in the form of their hold within the colonies, were all important in shaping what path colonisers eventually took for the institutional transfer. Based on these historical evidences, it is concluded that colonial institutions cannot be assumed as an exogenous transfer based on the notion of settlement as per AJR, rather it can be best described as an evolving fit between colonial and pre-colonial institutions. Keywords: Acemoglu, Johnson, and Robinson’s (2001, 2002), Reversal of Fortune, Institutions, Colonialism, Long-term Development Differences